EPIDEMIOLOGY OF DEPRESSION IN DIABETES PATIENTS: A CROSS-SECTIONAL STUDY CONDUCTED AT A TERTIARY CARE INSTITUTION. - Sahu, Himanshu Sekhar; Rajyalakshmi, Sai Venkata (Student's Journal of Health Research Africa, 2024)
Background Food habits and sedentary lifestyles have a substantial impact on mental and physiological health. The rise in the number of patients suffering from diabetes mellitus is exponential. Diabetes and depression both spread widely, and the association between diabetes and depression has been reported in previous studies. This study aims to determine the prevalence of depression among patients with diabetes and to investigate the association between diabetes-related factors, sociodemographic factors, and the occurrence of depression. Method This observational study was conducted prospectively at Narayana Medical College, Nellore. 109 patients who visited the outpatient department of the medical college were considered for this study. The sociodemographic profile of the patients was determined by interviewing them. The occurrence of depression was correlated with diabetes-related factors and sociodemographic factors. Results The study included both men and women, however over 60% were men. Study participants were mostly 50–60 years old. More than 70% of study participants reported Beck Depression Inventory scores over 16, suggesting depression and development. In the 50–60 age range, 42 of 43 patients experienced depression. Depression was correlated with age (p=0.032), gender (p=0.046), marital status (p=0.038), BMI (p=0.042), fasting blood sugar levels (p=0.029), HbA1c levels (p=0.039), and diabetes duration (p=0.037). Conclusion In this study, it was found that over 70% of the diabetics participating in this had depression. Most of the patients participating in this study were males belonging to the age group of 50 to 60 years. Diabetes and depression were found to be associated in the population participating in this study. Recommendation More such studies are required with large cohorts and inclusive of various geographical locations are required.